Nanomedicine as a Promising Tool to Overcome Immune Escape in Breast Cancer - Alba Navarro-Ocón; Jose L. Blaya-Cánovas; Araceli López-Tejada; Isabel Blancas; Rosario M. Sánchez-Martín; María J. Garrido; Carmen Griñán-Lisón; Jesús Calahorra; Francisca E. Cara; Francisco Ruiz-Cabello; Juan A. Marchal; Natalia Aptsiauri; et al. (MDPI AG, 2022)
Breast cancer is the most common type of malignancy and leading cause of cancer death among women worldwide. Despite the current revolutionary advances in the field of cancer immunotherapy, clinical response in breast cancer is frequently below expectations, in part due to various mechanisms of cancer immune escape that produce tumor variants that are resistant to treatment. Thus, a further understanding of the molecular events underlying immune evasion in breast cancer may guarantee a significant improvement in the clinical success of immunotherapy. Furthermore, nanomedicine provides a promising opportunity to enhance the efficacy of cancer immunotherapy by improving the delivery, retention and release of immunostimulatory agents in targeted cells and tumor tissues. Hence, it can be used to overcome tumor immune escape and increase tumor rejection in numerous malignancies, including breast cancer. In this review, we summarize the current status and emerging trends in nanomedicine-based strategies targeting cancer immune evasion and modulating the immunosuppressive tumor microenvironment, including the inhibition of immunosuppressive cells in the tumor area, the activation of dendritic cells and the stimulation of the specific antitumor T-cell response.